Economic analysis and marketing system of Apis mellifera honey production in Dang, Nepal - Budhathoki-Chhetri, Pratibha; Sah, Srawan Kumar; Regmi, Mahesh; Baral, Sabitri (Journal of Agriculture and Natural Resources, 2021)
Dang valley, the major honey producing district in Nepal, contributes 14 percent of national honey production in the country. Understanding the constraints and opportunities contributes in improving production and productivity of honey bee (Apis mellifera), in Dang, the study was initiated to find out the status, constraints and opportunities of honey production and its marketing system in the valley so as to increase the productivity and effective marketing. Total 60 beekeepers, 35 from Ghorahi and 25 from Tulsipur sub-metropolitan municipality having more than 20 beehives were selected based on proportionate stratified random sampling method and 2 processor cum wholesalers, 2 retailers, 2 middlemen and 2 cooperatives were selected based on simple random sampling method for interview. Personal interview, focus group discussion, key informant survey was used to collect primary data and secondary data were collected from topic related publications of various institution. The average annual honey productivity was 23.5 kg/hive with benefit cost ratio of 2.15 in 2019/20. Producers disposed their honey through nine marketing channels. Out of nine honey marketing channels, maximum portion i.e. 54.14% of honey disposed through producers to processor cum wholesalers to retailers/ traders inside or outside Dang to consumers, and only 2.66% of honey disposed through producers to cooperatives to consumers. Strengthening the appropriate management practice, quality testing and product certification of honey is must to enhance production and marketing of honey.